Mobile Computing and Communications: An Introduction - Othman, Mazliza (Malaysian Journal of Computer Science, 2017)
This paper gives an overview of mobile computing and issues related to the field. The discussion starts with definitions of various terms associated with mobile computing. The diversity of mobile applications is explored to give readers an idea of what mobile computing has to offer, followed by a discussion on the limitations of wireless networks and the issues which have to be addressed in order to support roaming users.